Odpowiedzi

2010-02-02T18:32:21+01:00
A) w(x)=4x⁵-4x⁴-24x³=4x³(x²-x-6)=4x³(x(x-1)-6)
b) w(x)=2x⁸-2x⁷+x⁶=x⁶(2x²-2x+1)=x⁶(2x(x-1)+1)
c) w(x)=2x⁶+2x⁵+3x⁴=x⁴(2x²+2x+3)=x⁴(2x(x+1)+3)
e) w(x)= 4x⁵+7x⁴-2x³=x³(4x²+7x-2)=x³(x(4x+7)-2)
f) w(x)= -30x⁵+60x⁴-90x³=30x³(-x²+2x-3)=30x³(-x(x-2)-3)

Proszę naj
2010-02-02T18:36:07+01:00
A) w(x)=4x⁵-4x⁴-24x³
4x^3(x^2-x-6)
b) w(x)=2x⁸-2x⁷+x⁶
2x^6(-x^2+x+1/2)
c) w(x)=2x⁶+2x⁵+3x⁴
2x^4(x^2+x+3/2)
e) w(x)= 4x⁵+7x⁴-2x³
2x^3(2x^2+7/2x-1)
f) w(x)= -30x⁵+60x⁴-90x³
30x^3(-x^2+2x-3)
1 1 1